1984
DOI: 10.1002/j.1556-6978.1984.tb00605.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Accredited Counselor Education Programs

Abstract: The Council for Accreditation of Counseling and Related Programs (CACREP) is a new accrediting agency (September of 1981). The purpose of this study was to survey the accredited programs of CACREP. Department heads from these programs were asked to respond to a number of questions concerning the characteristics of their faculty, students, program, and admission criteria. The majority of departments reported that the accreditation procedure had a significant positive impact on their program. Descriptive data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Once CACREP was established, several articles related survey results focused on specific accreditation concerns. Data have been generated on the quality and types of entering graduate students' concerns (Stickle & Schnacke, 1984) related to increases in program requirements (Cecil & Comas, 1986;Vacc, 1985), accredited program faculty characteristics (Miller & Sampson, 1984), and program intentions for seeking CACREP accreditation (Cecil et al, 1987). Because these early surveys were limited by the relatively low number of CACREP programs available for response, low response rates, or both, generalizations for use by CACREP have been avoided.…”
mentioning
confidence: 99%
“…Once CACREP was established, several articles related survey results focused on specific accreditation concerns. Data have been generated on the quality and types of entering graduate students' concerns (Stickle & Schnacke, 1984) related to increases in program requirements (Cecil & Comas, 1986;Vacc, 1985), accredited program faculty characteristics (Miller & Sampson, 1984), and program intentions for seeking CACREP accreditation (Cecil et al, 1987). Because these early surveys were limited by the relatively low number of CACREP programs available for response, low response rates, or both, generalizations for use by CACREP have been avoided.…”
mentioning
confidence: 99%
“…R esearchers have concluded that CACREP (Council for Accreditation of Counseling and Related Educational Programs) accredited programs are in a more advantageous and competitive position regarding such factors as increased student and faculty pride, university support, faculty involvement, and increased student enrollment (Cecil & Comas 1986;Cecil et al, 1987;Stickle & Schnacke, 1984;Vacc, 1985). Yet, the quintessential issue for counselor educators to consider when applying for accreditation by CACREP is whether the Standards for the Preparation of Counselors are relevant to counselor education.…”
mentioning
confidence: 99%
“…Regarding CACREP accreditation, earlier surveys of counselor educators have indicated that the payoff from the large effort required to complete the accreditation process successfully is worth the effort (Cecil & Comas, 1986;Stickle & Schnacke, 1984). The experience at SUNY Plattsburgh substantiates this view; this is addressed later in this article.…”
Section: Basic Issuesmentioning
confidence: 79%